Cyber crime and the victimization of women : laws, rights and regulations - Halder, Debarati, 1975-; Jaishankar, K. (Hershey, PA : Information Science Reference, 2012)
'This book investigates cyber crime, exploring gendered dimensions of cyber crimes like adult bullying, cyber stalking, hacking, defamation, morphed pornographic images, and electronic blackmailing'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Sex crimes; Computer crimes; Women -- Crimes against